Behavioural activation and inhibition systems in relation to pain intensity and duration in a sample of people experiencing chronic musculoskeletal pain. (June 2020) - Sanson, Nina; Hach, Sylvia; Moran, Robert; Mason, Jesse
Abstract: Background: There is potential clinical utility in tailoring patients' pain management based on behavioural tendencies. Previous work demonstrates a link between behavioural approach/inhibition and pain experience. Objectives: To investigate the relationship of pain intensity and duration with behavioural activation and inhibition tendencies and fear-avoidance beliefs, kinesiophobia, and disability, in a sample group ( n  = 709) reporting chronic musculoskeletal pain. Methods: Regression analyses assessed the predictive value of these variables on pain intensity and on pain duration. Differences in behavioural tendencies between groups reporting high and low pain intensities were examined. Results: Neither pain intensity nor pain duration were correlated with behavioural activation (BAS) and inhibition (BIS). Both pain intensity and duration were correlated with fear-avoidance beliefs (intensity p  < .001, duration p  = .005), kinesiophobia (intensity and duration both p  < .001, and disability (intensity and duration both p  < .001). There were significant positive relationships between pain intensity and fear-avoidance beliefs ( p  < .001), kinesiophobia ( p  = .021), and disability ( p  < .001), as well as positive relationships between pain duration and fear-avoidance ( p  = .543), kinesiophobia ( p  = .084) and disability ( p  = .002). Fear-avoidance beliefs, kinesiophobia and disability accounted for 31% of the variance in pain intensity. Conclusions: Neither BIS nor BAS significantly related to, or predicted pain intensity or duration. No differences in activation and inhibition tendencies were evident between high and low pain intensity groups. This study provides further support for the inter-relationships between fear-avoidance beliefs, kinesiophobia, disability and pain duration and intensity. No explicit support for behavioural links to pain were shown, however, this may be due to the measurement instrument rather than an invalid theory. Highlights: Fear-avoidance beliefs, kinesiophobia and disability largely accounted for pain intensity variance. Behavioural inhibition/activation did not relate to, or predict, pain intensity or duration. There was no explicit support for behavioural links to pain.